An Introduction to Roswitha Scholz's Feminist Theory: The capitalist patriarchy of the value/split form - Torres Gaxiola, Andrea (2025)
This paper intends to be a short introduction to Roswitha Scholz’s critique of the political economy of gender, as a feminist reading and reformulation of Karl Marx’s labour theory of value. In the first place, we analyze the criticism to traditional marxism that Moishe Postone carries out, as well as Roswitha Scholz’s critique to feminist marxism.  We intend to show that Roswitha Scholz critique of value aims to validate gender as a central category for a critical theory of capitalism and of the oppression of women. Secondly, we analyze the  core elements of Roswitha Scholz’s value-dissociation form theory. Lastly, we review its implications and its grasp of the oppression and emancipation of women.